Application of Lev Vygotsky’s Theory in Social Studies Learning Using Social Action Projects Based on Creative Pedagogy to Increase Student Engagement - Anik Widiastuti; Nana Supriatna; Disman Disman; Siti Nurbayani K (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teachers were forced to manage long-distance learning during the Covid-19 pandemic, but student’s engagement was less satisfying. This situation would impact on students’ learning achievement. In responding to these challenges, lesson design using the social action project based on creative pedagogy models can be used as an alternative to activate students’ engagement in post-pandemic Social Studies learning in junior high schools. This study aimed to explore the application of Lev Vygotsky's theory, especially related to the use of social action project based on creative pedagogy in social studies learning. The research model used is descriptive qualitative from the results of interviews and observations. The data sources are a social studies teacher and 5 students who are the group leader. The results showed that application of Lev Vygotsky’s theory occurs at every step in social action project based on creative pedagogy models. Scaffolding and the role of more knowledgeable others in social studies learning using that models help student development, increases student engagement, and also helps the teacher to manage class more effectively. It is concluded that the application of Lev Vygotsky’s theory in Social Studies learning using social action project based on creative pedagogy performs in student’s creative learning supported by a teacher’s creative teaching can increase students engagement.